Copyright

Solve the equation.3z+6z+7=29-4

Question:

Solve the equation.

{eq}3z + 6z + 7 = 29 - 4 {/eq}

Algebraic Expression

An algebraic expression is a mathematical statement that contains numbers and variables. These are solved by manipulating the expressions following mathematical rules.

Answer and Explanation:

Solving for {eq}z {/eq} in the equation requires collecting like terms first:

{eq}3z + 6z + 7 = 29 -4 {/eq}

{eq}3z + 6z = 29 -4-7 {/eq}

{eq}9z = 29 -11 {/eq}

{eq}9z = 18 {/eq}

Dividing both sides by 9:

{eq}\displaystyle \frac{9z}{9} = \frac{18}{9} {/eq}

{eq}z = 2 {/eq}

To check, substitue the value in the original equation:

{eq}3z + 6z + 7 = 29 -4 {/eq}

{eq}3(2) + 6(2) + 7 \stackrel{?}{=} 29 -4 {/eq}

{eq}6 + 12 + 7 \stackrel{?}{=} 25 {/eq}

{eq}25 \stackrel{\checkmark}{=} 25 {/eq}

Thus, the value of {eq}z {/eq} is {eq}2 {/eq}.


Learn more about this topic:

Loading...
Evaluating Simple Algebraic Expressions

from ELM: CSU Math Study Guide

Chapter 6 / Lesson 3
75K

Related to this Question

Explore our homework questions and answers library